Biological therapy for psoriasis and risk of cancer. (1st October 2018) - Garcia‐Doval, I.; Descalzo, M.A.; Mason, K.J.; Cohen, A.D.; Ormerod, A.D.; Gómez‐García, F.J.; Cazzaniga, S.; Feldhamer, I.; Ali, H.; Herrera‐Acosta, E.; Griffiths, C.E.M.; Stern, R.; et al.
Summary: Psoriasis is a common skin disease that affects up to 3% of people worldwide. Psoriasis is driven by faults in the immune system (which protects the body from infection), which leads to excess skin production. People with the most severe form of psoriasis are given therapies to dampen down the immune system. Systemic therapies (methotrexate and ciclosporin) work to reduce the whole immune system, while biologic therapies (adalimumab, etanercept, and ustekinumab) are targeted to specific immune pathways in the skin. However, there is concern that these therapies may increase the risk of cancer. This study of psoriasis patients in Ireland, Israel, Italy, Spain, and the U.K. aimed to find out if the amount of time spent on these therapies increases the risk of cancer. Each person who developed a cancer during the study was compared to four cancer‐free psoriasis patients (controls) of the same sex, age, dermatology centre, and year of entry into the study. The total time spent on systemic and biologic therapies was calculated for each patient. The authors did not find a difference in the time spent on systemic or biologic therapies between patients who developed a cancer and controls. This result remained unchanged after considering the possible effects of previous exposure to other systemic therapies, duration of psoriasis, smoking, previous exposure to phototherapy and other simultaneous diseases. This study showed that cancers were not more likely to develop after up to 8 years of treatment with biologic therapies.